Epidermal nerve fibers: Confidence intervals and continuous measures with nerve conduction - Engelstad, JaNean K. (Lippincott Williams & Wilkins, 2012)
OBJECTIVES: Our first objective was to explore the value of estimating 95% confidence intervals (CIs) of epidermal nerve fibers (ENFs)/mm for number of sections to be evaluated and for confidently judging normality or abnormality. Our second objective was to introduce a new continuous measure combining nerve conduction and ENFs/mm. METHODS: The 95% CI studies were performed on 1, 1–2, 1–3 - - - 1–10 serial skip sections of 3-mm punch biopsies of leg and thigh of 67 healthy subjects and 23 patients with diabetes mellitus. RESULTS: Variability of differences of ENFs/mm counts (and 95% CIs) from evaluation of 1, 1–2, 1–3 - - - 1–9 compared with 1–10 serial skip sections decreased progressively without a break point with increasing numbers of sections evaluated. Estimating 95% CIs as sections are evaluated can be used to judge how many sections are needed for adequate evaluation, i.e., only a few when counts and 95% CIs are well within the range of normality or abnormality and more when values are borderline. Also provided is a methodology to combine results of nerve conduction and ENFs/mm as continuous measures of normality or abnormality. CONCLUSION: Estimating 95% CIs of ENFs/mm is useful to judge how many sections should be evaluated to confidently declare counts to be normal or abnormal. Also introduced is a continuous measure of both large-fiber (nerve conduction) and small-fiber (ENFs/mm) normal structures/functions spanning the range of normality and abnormality for use in therapeutic trials.